New Horizons for Asian Museums and Museology - Sonoda, Naoko; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book presents up-to-date information about museums and museology in present-day Asia, focusing on Japan, Mongolia, Myanmar, and Thailand. Asian countries today have developed or are developing their own museology and museums, which are not simple copies of European or North American models. This book provides readers with carefully chosen examples of museum activities$1 (Bfor example, exhibition and sharing information, database construction, access to and conservation of museum collections, relationships between museums and local communities, and international cooperation in the field of cultural heritage. Readers are expected to include museum professionals and museology students. Throughout the course of this book, the reader will understand that a museum is not only a place for collecting, representing, and preserving cultural heritage but also plays a fundamental role in community development. This book is highly recommendedto readers who seek a worldwide vision of museum studies. The peer-reviewed chapters in this volume are written versions of the lectures delivered by selected speakers at the international symposium "New Horizons for Asian Museums and Museology" held in February 2015 at the National Museum of Ethnology, Japan.s
Keywords: Cultural property; Archaeology; Cultural Heritage; Archaeology